Google Cloud cookbook : practical solutions for building and deploying cloud services - Costa, Rui (Software engineer); Hodun, Drew (Ascent Audio, 2022)
Get quick hands-on experience with Google Cloud. This cookbook provides a variety of self-contained recipes that show you how to use Google Cloud services for your enterprise application. Whether you're looking for practical ways to apply microservices, AI, analytics, security, or networking solutions, these recipes take you step-by-step through the process and provide discussions that explain how and why the recipes work. Ideal for system engineers and administrators, developers, network and database administrators, and data analysts, this cookbook helps you get started with Google Cloud regardless of your level of experience. Google veterans Rui Costa and Drew Hodun also cover advanced-level Google Cloud services for those who have appreciable experience with the platform. With this book, you'll learn how to get started with Google Cloud; understand the depth of services Google Cloud provides; gain hands-on experience using practical examples and labs; explore topics that include BigQuery, Cloud Run, and Kubernetes; build and run mobile and web applications on Google Cloud; examine ways to build your cloud applications for scale; build a minimum viable product (MVP) app to use in production; and learn data platform and pipeline skills.